تحسين أداء واستقرار أنظمة القيادة متغيرة السرعة بمقوم 12 نبضه في المنشآت الصناعية الحديثة - غسان حايك; بسام عطية; صفوان نضوه (Tishreen University, 2018)
يعرض هذا البحث استخدام دارة مقطع الأرباع الأربعة في حلقة التيار المستمر لنظام قيادة متغير السرعة ذي مقوم ديودي 12 نبضة بهدف تحسين مواصفات الجودة في شبكة التغذية وتقليل كل من عاملي التموج و الذروة  للجهد والتيار في حلقة التيار المستمر وتحسين استقرار نظام القيادة. تمت نمذجة ومحاكاة نظام القيادة متغير السرعة مع مقوم ديودي 12 نبضة، وذللك لتأكيد إمكانية استخدام مقطع الأرباع الأربعة مع مخططات دارات التقويم المختلفة وتحسين استقرار أنظمة القيادة الموجودة في المنشآت الصناعية الحديثة. This paper suggests improving the quality and performance of electrical grid by using Four Chopper circuit in the DC -Link of the variable speed drive system with 12 pulse rectifier. In addition, it analyses the effects on the ripple factor for both current and voltage in DC-link and improving the system's stability. For this study a variable speed drive system has been simulated and designed with the proposed chopper and 12 pulse rectifiers. In order to confirm the ability of Using four - quadrant chopper with rectifier circuits and its ability to improve the stability of the power systems, a variable speed system has been simulated Finally, A discussion of the results was introduced. The giving results show the advantages of using the proposed chopper with variable speed drive systems.